Evaluation of Mendeley Utilization Training in Writing Scientific Papers Based on the Goal-Oriented Evaluation Model - Waruwu, Marinu; Halida; Pu'at, Siti Natijatul; Rusydiana, Marwah; Sabila, Dias Khairina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on the world of education. One of these impacts is the use of the Mendeley application in writing scientific papers by students. The purpose of this study was to test the effectiveness of training in using Mendeley in writing scientific papers for students. Participants in this study were 21 students. The method used in this study is a mixed method, which combines qualitative and quantitative approaches. Qualitative data collection techniques were conducted through interviews, observations, and document studies, while quantitative data were collected using questionnaires involving 21 participants from among students. The data obtained were analyzed qualitatively using the Miles and Huberman analysis model and quantitatively using descriptive statistics to calculate the mean and percentage. The results of the study showed a good level of achievement regarding the set training objectives. Most participants succeeded in increasing the expected knowledge and skill competencies. However, there were variations in achievement among participants, mainly influenced by their level of participation and background. This study was limited by the sample, which only consisted of seventh-semester students. Further research is recommended to be conducted on a wider scale with more complex sample characteristics. Therefore, long-term evaluation is needed to ensure the sustainability of the training impact, and higher education institutions should integrate this training program into student competency development initiatives to improve the quality of academic writing.